An introduction to the topological derivative. Issue 1 (28th September 2021) - Amstutz, Samuel
Abstract : Purpose: This paper provides a self-contained introduction to the mathematical aspects of the topological derivative. Design/methodology/approach: Full justifications are given on simple model problems following a modern approach based on the averaged adjoint state technique. Extensions are discussed in relation with the literature on the field. Findings: Closed expressions of topological derivatives are obtained and commented. Originality/value: Several cases are covered in a unified and didactic presentation. Some elements of proof are novel.